Interwoven carbon nanotube-poly(acrylic acid) network scaffolds for stable Si microparticle battery anode. (15th January 2023) - Lee, Gwanghyun; Choi, Yunkyu; Ji, Hyungjoon; Kim, Ju Yeon; Kim, Jeong Pil; Kang, Junhyeok; Kwon, Ohchan; Kim, Dae Woo; Park, Jong Hyeok
Abstract: A highly stable silicon microparticle (μSi) anode with high energy density is reported using a hybrid binder made of functionalized carbon nanotubes (FCNTs) and poly(acrylic acid) (PAA). The FCNTs with high electrical conductivity can be stably dispersed in water after partial oxidation of the carbon nanotubes (CNTs), forming a macroporous scaffold in an aqueous dispersion. By mixing the FCNT scaffold with PAA and μSi particles, FCNT/PAA uniformly encapsulates μSi and can be easily coated on Cu foil via a practical bar-coating method without the use of harsh solvents, stabilizers, or additional processes. The μSi-FCNT-PAA electrode exhibits stable performance, with an initial reversible capacity of 3560 mAh g −1 at 1C and a specific capacity of 1764 mAh g −1 at 200 cycles in a half-cell test. Full-cell test with NCM 712 cathode also shows stable capacity retention at 1C, exhibiting an initial reversible capacity of 170 mAh g −1 and a specific capacity of 81 mAh g −1 at 200 cycles. The FCNT network with enhanced mechanical properties due to the addition of PAA is effective in preserving the Si anode structure during cycling tests by enduring its volume changes and preventing thick solid-electrolyte interphase (SEI) layer formation. Graphical abstract: Image 1 Highlights: Anode was prepared with water soluble functionalized carbon nanotube (FCNT). FCNT formed conductive network by encapsulating silicon microparticle (μSi). Poly(acrylic acid) (PAA) enhanced flexibility and formation of conductive network. Flexible conductive network suppressed pulverization and isolation of μSi. The anode retained high capacity and long cycle stability in half/full cell system.